Reductions in anxiety and depression symptoms in a subset of outpatients with problematic substance use who received ketamine-assisted psychotherapy: a two-year retrospective chart review - Whinkin, Emily; Eparwa, Therry Rose J.; Julseth, Michelle C.; Schneider, Andrea; Aggarwal, Sunil K. (Frontiers in Psychiatry, 2023)
Objective Assess changes in symptoms of anxiety, depression, and psychosocial or spiritual distress before and after ketamine-assisted psychotherapy (KAP) in individuals with problematic substance use (PSU). Methods A retrospective chart review was performed on participant data from two five-year prospective outcomes studies: the AIMS Medical Outcomes Study (AMOS) and the AIMS Cancer Outcomes Study (ACOS). The efficacy of KAP for anxiety, depression, and psychosocial or spiritual well being was assessed in patients with current, past, or high risk of substance use disorder. Validated psychometrics utilized were Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and the National Institute of Health - Healing Experiences of All Life Stressors (NIH-HEALS) questionnaires. Results Between November 1, 2020 and October 31, 2022, a total of 18 patients identified with problematic substance use completed at least one KAP session and at least one baseline and post-KAP metric questionnaire. The PSU subpopulation average score changes were as follows: GAD-7 (-6.71 ± 9.15, n = 14); PHQ-9 (-7.44 ± 5.42, n = 16); and NIH-HEALS (5.13 ± 13.64, n = 15). The average score changes for the KAP population of enrolled subjects were as follows: GAD-7 (-2.45 ± 6.01, n = 104); PHQ-9 (-3.02 ± 6.01, n = 111); and NIH-HEALS (2.93 ± 11.91, n = 86). A comparison of average score changes (p < 0.05) between the PSU subpopulation and KAP population were as follows: GAD-7 (0.0219, 95% C.I. 1.37-8.11); PHQ-9 (0.0062, 95% C.I. 1.28-7.56); and NIH-HEALS (0.5197, 95% C.I. 8.96-4.56). For patients with PSU, results demonstrate statistically significant improvements in anxiety and depression symptoms after at least one KAP session. Average NIH-HEALS scores increased, though not by a statistically significant amount. Compared to the general population of enrolled KAP patients during this period, patients with PSU reported significantly greater average reductions in GAD-7 and PHQ-9 scores. Conclusion Undergoing one to six ketamine-assisted psychotherapy (KAP) sessions was associated with improved anxiety and depression ratings in patients with problematic substance use. Two-thirds of participants also experienced improved psychosocial and spiritual well-being. The use of KAP may be important to consider as a therapy for reducing anxiety and depression symptoms in patients with problematic substance use.